2019
DOI: 10.3390/antibiotics8030133
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Ribosome Engineering to Natural Product Discovery and Yield Improvement in Streptomyces

Abstract: Microbial natural product drug discovery and development has entered a new era, driven by microbial genomics and synthetic biology. Genome sequencing has revealed the vast potential to produce valuable secondary metabolites in bacteria and fungi. However, many of the biosynthetic gene clusters are silent under standard fermentation conditions. By rational screening for mutations in bacterial ribosomal proteins or RNA polymerases, ribosome engineering is a versatile approach to obtain mutants with improved tite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 99 publications
0
37
0
Order By: Relevance
“…It is well known that rpoB gene mutations, which arose in the RNA polymerase (RNAP) βsubunit, are responsible for the acquisition of rifampicin resistance and quite effective for activating the poorly expressed or silent secondary metabolite biosynthetic genes [23,24]. Rifampicin resistance mutations are usually located in one specific conserved region of the Rif cluster within positions 1264C to 1327G, representing amino acid residues Leu422 to Ala443 [14]. It is reported that rpoB H437Y (His437 to Tyr) and H437R (His437 to Arg) mutations were most often effective in a wide variety of actinomycetes [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that rpoB gene mutations, which arose in the RNA polymerase (RNAP) βsubunit, are responsible for the acquisition of rifampicin resistance and quite effective for activating the poorly expressed or silent secondary metabolite biosynthetic genes [23,24]. Rifampicin resistance mutations are usually located in one specific conserved region of the Rif cluster within positions 1264C to 1327G, representing amino acid residues Leu422 to Ala443 [14]. It is reported that rpoB H437Y (His437 to Tyr) and H437R (His437 to Arg) mutations were most often effective in a wide variety of actinomycetes [16].…”
Section: Discussionmentioning
confidence: 99%
“…The "ribosome engineering" technology is an extremely effective method to increase activation of poorly expressed and cryptic genes in bacteria through the modulation of ribosomal components [10,11]. It has been applied on antibiotic overproduction and new active compound discovery in recent years because of its simplicity, wide applicability, and scalability for large-scale production [12][13][14][15]. This approach is based on the introduction of genetic mutations that confer resistance to drugs which target the ribosome, including streptomycin, gentamicin, paromomycin, neomycin, and others [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosome engineering is an approach to discover microbes with certain spontaneous mutations in their ribosome or RNA polymerase, through screening antibiotic-resistant mutants on Petri dishes ( Zhu et al, 2019 ). It is suitable for gene activation and strain improvement, resulting in the identification of novel secondary metabolites, as well as the enhancement of enzyme production and tolerance to toxic chemicals ( Ochi, 2017 ).…”
Section: In Situ Activation Of Target Bgcsmentioning
confidence: 99%
“…Strains that become resistant to these antibiotics harbour mutations in the ribosome. Resistance to other ribosome targeting antibiotics such as gentamicin or erythromycin could also stimulate antibiotic production (Hosaka et al 2009 ; Zhu et al 2019 ).…”
Section: Background: the Antibiotic Resistance Global Threat And Currmentioning
confidence: 99%